Edge strength of CAD/CAM materials. (July 2018) - Pfeilschifter, Maria; Preis, Verena; Behr, Michael; Rosentritt, Martin
Abstract: Objectives: To investigate the edge force of CAD/CAM materials as a function of (a) material, (b) thickness, and (c) distance from the margin. Methods: Materials intended for processing with CAD/CAM were investigated: eight resin composites, one resin-infiltrated ceramic, and a clinically proven lithiumdisilicate ceramic (reference). To measure edge force (that is, load to failure/crack), plates (d = 1 mm) were fixed and loaded with a Vickers diamond indenter (1 mm/min, Zwick 1446) at a distance of 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, and 1.0 mm from the edge. Edge force was defined as a loading force at a distance of 0.5 mm. The type of failure was determined. To investigate the influence of the thickness, all data were determined on 1-mm and 2-mm plates. To test the influence of bonding and an underlying dentin, individual 1-mm plates were bonded to a 1-mm-thick dentin-like (concerning modulus of elasticity) resin composite. Results: For the 1-mm plates, edge force varied between 64.4 ± 24.2 N (Shofu Block HC) and 183.2 ± 63.3 N (ceramic reference), with significant ( p ≤ 0.001) differences between the materials. For the 2-mm plates, values between 129.2 ± 32.5 N (Lava Ultimate) and 230.3 ± 67.5 N (Cerasmart) were found. Statistical comparison revealed no significant differences ( p > 0.109) between the materials. Brilliant Crios ( p = 0.023), Enamic ( p = 0.000), Shofu Blocks HC ( p = 0.009), and Grandio Bloc ( p = 0.002) showed significantly different edge force between the 1-mm- and 2-mm-thick plates. The failure pattern was either cracking, (severe) chipping, or fracture. Conclusions: Material, material thickness, and distance from the edge impact the edge force of CAD/CAM materials. Clinical significance: CAD/CAM materials should be carefully selected on the basis of their individual edge force and performance during milling.